Media Sosial Sebagai Teknologi Informasi Penggerak Percepatan Pemanfaatan Potensi Desa Mekarjaya Ciawigebang Kuningan - Fauziah; Aah Sumiah; Dede Irawan; Harun Assidik; Abdul Aziz Alfarizy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Kuningan, 2023)
Information technology can be a link between one person and many people which allows information to be conveyed quickly. Social media is one way that information can be conveyed to the public by providing benefits that can attract many groups, parents, children, teenagers, entrepreneurs, educators, workers, etc. With social media, the information that you want to spread to advance a business from a potential community in rural areas, especially in Mekarjaya Village, is still felt to be underused because one of the factors is that most of the users of social media are young people, while in Mekarjaya Village, most of the farmers are people who already old age. The total population of the country of Indonesia is 256.4 million people, as many as 130 million people or around 49 percent of them are active users of social media. Social media-based information technology seminars for the people of Mekarjaya village to be able to develop village potential products and provide economic benefits for the community and expand their reach to areas in need. This seminar is summarized in the Community Service Activities (PkM) program organized by Kuningan University by involving lecturers and students as a form of community service to improve society's quality.